Epigenetic repression of miR‐375 is the dominant mechanism for constitutive activation of the PDPK1/RPS6KA3 signalling axis in multiple myeloma. (25th April 2017) - Tatekawa, Shotaro; Chinen, Yoshiaki; Ri, Masaki; Narita, Tomoko; Shimura, Yuji; Matsumura‐Kimoto, Yayoi; Tsukamoto, Taku; Kobayashi, Tsutomu; Kawata, Eri; Uoshima, Nobuhiko; Taki, Tomohiko; Taniwaki, Masafumi; et al.
Summary: Cytogenetic/molecular heterogeneity is the hallmark of multiple myeloma (MM). However, we recently showed that the serine/threonine kinase PDPK1 and its substrate RPS6KA3 (also termed RSK2) are universally active in MM, and play pivotal roles in myeloma pathophysiology. In this study, we assessed involvement of aberrant miR‐375 repression in PDPK1 overexpression in MM. An analysis of plasma cells from 30 pre‐malignant monoclonal gammopathies of undetermined significance and 73 MM patients showed a significant decrease in miR‐375 expression in patient‐derived plasma cells regardless of the clinical stage, compared to normal plasma cells. Introduction of miR‐375 reduced PDPK1 expression in human myeloma cell lines (HMCLs), indicating that miR‐375 is the dominant regulator of PDPK1 expression. In addition, miR‐375 introduction also downregulated IGF1R and JAK2 in HMCLs. CpG islands in the MIR375 promoter were pathologically hypermethylated in all 8 HMCLs examined and in most of 58 patient‐derived myeloma cells. Treatment with SGI‐110, a hypomethylating agent, and/or trichostatin A, a histone deacetylase inhibitor, increased miR‐375 expression, but repressed PDPK1, IGF1R and JAK2 in HMCLs. Collectively, these results show the universal involvement of overlapping epigenetic dysregulation for abnormal miR‐375 repression in MM, which is likely to contribute to myelomagenesis and to subsequent myeloma progression by activating oncogenic signalling pathways.